The Power of Information in Public Services: Evidence from Education in Uganda - Reinikka, Ritva; Svensson, Jakob (2012)
In this paper we argue that innovations in governance of social services are an effective way to improve outcomes such as attainment of universal primary education. To test this hypothesis we exploit an unusual policy experiment: a newspaper campaign in Uganda aimed at reducing the capture of public funds by providing schools (parents) with systematic information to monitor local officials' handling of a large education grant program. Combining survey and administrative data, we show that public access to information can be a powerful deterrent to the capture of funds at the local level and that the reduction in the capture of funds that resulted had a positive effect on school enrollment and learning outcomes.